(untitled) (Research, Society and Development, 2020)
Products of natural origin with potential chelating or reducing Fe+ free become promising in antioxidant research, because they have the ability to soften transition metals that can cause cellular damage by oxidative stress. Thus, the aim of this study is to promote the evaluation of the antioxidant potential of essential oil by the orthophenanthroline method, in addition to promoting phytochemical analysis of the essential oil of M. suaveolens. This vegetable, by other antioxidant methods, has promising properties in inhibiting free radicals. To achieve these objectives, a chromatographic analysis was performed, as well as the orthophenanthroline assays to evaluate the formation of the Fe2+ 1,10-orthophenanthroline complex. The β-Caryophyllene (20.38%) stands out as the major compound of the species. The essential oil interfered with the formation of the complex, suggesting a moderate chelating activity at the highest concentration tested (480 µg/mL), demonstrating that the oil can chelate Fe2+. The addition of ascorbic acid to the mixture significantly increased the absorbance for all tested concentrations, in the evaluation of the reducing power from Fe3+ to Fe2+. Considering a potential source of natural antioxidants, it may be relevant for the management of oxidative stress.